2020
DOI: 10.25083/rbl/25.1/1289.1295
|View full text |Cite
|
Sign up to set email alerts
|

Biases of Shear Wave vs Transient Elastography in fibrosis assessment of patients with fatty liver disease

Abstract: Background: The assessment of fibrosis in chronic liver diseases using non-invasive methods is an important topic in hepatology. Aim: To compare Shear Wave and Transient elastography and in what the possible measurement biases and discordance factors are concerned. Material and Methods: This study enrolled 139 patients with non-alcoholic fatty liver disease, who underwent assessment of hepatic fibrosis by Shear Wave and Transient elastography. Results: The results obtained by the two methods were correlated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[40] For Olteanu et al, the BMI, the level of necrotic-inflammatory activity and hepatic steatosis, significantly influence the correlation between the FS and SWE values (p respectively at 0.0020; 0.001; 0.004). [41] Conversely, Herman et al reported a good significant correlation with the FS and SWE values in the assessment of a liver fibrosis in NAFLD patients. [35] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[40] For Olteanu et al, the BMI, the level of necrotic-inflammatory activity and hepatic steatosis, significantly influence the correlation between the FS and SWE values (p respectively at 0.0020; 0.001; 0.004). [41] Conversely, Herman et al reported a good significant correlation with the FS and SWE values in the assessment of a liver fibrosis in NAFLD patients. [35] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 95%
“…[ 40 ] For Olteanu et al, the BMI, the level of necrotic-inflammatory activity and hepatic steatosis, significantly influence the correlation between the FS and SWE values (p respectively at 0.0020; 0.001; 0.004). [ 41 ]…”
Section: Discussionmentioning
confidence: 99%